2020
DOI: 10.1186/s13075-020-02260-6
|View full text |Cite
|
Sign up to set email alerts
|

Initiating guideline-concordant gout treatment improves arterial endothelial function and reduces intercritical inflammation: a prospective observational study

Abstract: Background: Patients with gout have arterial dysfunction and systemic inflammation, even during intercritical episodes, which may be markers of future adverse cardiovascular outcomes. We conducted a prospective observational study to assess whether initiating guideline-concordant gout therapy with colchicine and a uratelowering xanthine oxidase inhibitor (XOI) improves arterial function and reduces inflammation. Methods: Thirty-eight untreated gout patients meeting American College of Rheumatology (ACR)/Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“… 35 , 36 A striking finding in gout is that resolution of an acute attack is not associated with resolution of urate crystals because they will persist until the next attack (i.e., the “intercritical period”). 37 These “silent crystals” can still be associated with evidence for systemic inflammation that may have an indirect role in the progression of kidney disease and cardiovascular events. 38 Indeed, both elevated monocyte counts and high levels of highly sensitive C-reactive protein levels are found in patients with a history of gout.…”
Section: Gout and Ckdmentioning
confidence: 99%
“… 35 , 36 A striking finding in gout is that resolution of an acute attack is not associated with resolution of urate crystals because they will persist until the next attack (i.e., the “intercritical period”). 37 These “silent crystals” can still be associated with evidence for systemic inflammation that may have an indirect role in the progression of kidney disease and cardiovascular events. 38 Indeed, both elevated monocyte counts and high levels of highly sensitive C-reactive protein levels are found in patients with a history of gout.…”
Section: Gout and Ckdmentioning
confidence: 99%
“…Chronic inflammation is a well-known etiology of anemia and a factor that leads to ESA resistance in patients on dialysis. (18) While gout is often thought of as a disease of intermittent acute inflammation that occurs only during gout flares, there is evidence that systemic inflammation persists in gout patients during asymptomatic (inter-critical) periods (19,20) Like other rheumatologic inflammatory diseases such as rheumatoid arthritis and systemic lupus erythematosus, gout inflammation's impact on cytokine production, (21,22) elevated hepcidin levels, and iron sequestration (18,23) may explain this unexpected finding.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that maintaining SU below 6 mg/dL decreases gout sequelae, including gout flares [ 28 , 29 ], tophi [ 29 , 30 ], and joint damage [ 28 ], and lower SU levels have been shown to speed these improvements [ 28 , 30 ]. Furthermore, a treat-to-target approach with ULTs has been shown to decrease systemic inflammation, even during asymptomatic, intercritical periods [ 12 ]. The current study further demonstrated the clinical benefits and quality of life improvement associated with rapid and sustained urate lowering.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperuricemia results in monosodium urate crystal deposition throughout the body, including in the kidneys, heart, larynx, and bowel [2], and is associated with a specific set of comorbidities, including cardiovascular disease [3][4][5][6][7], hypertension [7,8], diabetes [7,9], and chronic kidney disease [7,10]. Even in patients with asymptomatic hyperuricemia, inflammation levels are elevated [11,12]. When oral urate-lowering therapies (ULTs), including both xanthine oxidase inhibitors [13] and uricosurics [13,14], are not tolerated, contraindicated, or no longer effective, refractory or uncontrolled gout can occur.…”
Section: Introductionmentioning
confidence: 99%